If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(n-2)=-3(2n-4)
We move all terms to the left:
5(n-2)-(-3(2n-4))=0
We multiply parentheses
5n-(-3(2n-4))-10=0
We calculate terms in parentheses: -(-3(2n-4)), so:We get rid of parentheses
-3(2n-4)
We multiply parentheses
-6n+12
Back to the equation:
-(-6n+12)
5n+6n-12-10=0
We add all the numbers together, and all the variables
11n-22=0
We move all terms containing n to the left, all other terms to the right
11n=22
n=22/11
n=2
| 3x-4=5x-50 | | y(y-1)(y+1)=3360 | | 8-4x=138 | | 8.8(x-3.5)=26.4 | | -5+2q=2q-5 | | 5/2u=1/10-7/5u | | 9x-5x+170=9x+60 | | n/10+2/5=-2/5 | | 6x+7=x+1 | | -4-6h=5-9h | | y-4=2(-3+3) | | -8m-6m-9=-23 | | 9j+6=2j-8 | | 4x+2x−3x=3 | | 31-3x=6(7x+4)+7 | | 2n-10=5+n | | 5w-4=-4+5w | | 23x-5=21x+5,x | | -5x+13+3x=9-7x-6 | | 93276029x+0941872=192640298365029 | | -1+9z=9z-8 | | 9-8z=-8z+9 | | 7(2x+3)=9(x+4) | | 5t^2-2t-2=0 | | (-460)=-10(5x+16) | | 8x-5(2x-6)=-x+30 | | 20f+11=19f | | -16j-18=-18j | | 22.94x=31.26 | | -15r=-17r+14 | | 12t+4t−14t−t+2=13 | | 13.82+0.13x=14.57+0.15x |